Compositional Constraint Is the Key Force in Shaping Codon Usage Bias in Hemagglutinin Gene in H1N1 Subtype of Influenza A Virus. (17th July 2014) - Deka, Himangshu; Chakraborty, Supriyo
Abstract : It is vital to unravel the codon usage bias in order to gain insights into the evolutionary forces dictating the viral evolution process. Influenza A virus has attracted attention of many investigators over the years due to high mutation rate and being cross-specific shift operational in the viral genome. Several authors have reported that the codon usage bias is low in influenza A viruses, citing mutational pressure as the decisive force shaping up the codon usage in these viruses. In this study, complete coding sequences of hemagglutinin genes for H1N1 subtype of influenza A virus have been explored for the possible codon usage bias acting upon these genes. The results indicate overall low bias with peaking ENC values. The GC content is found to be substantially low as against AT content in the silent codon sites. Significant correlations were observed in between the compositional parameters versus AT3, implying the possible role of the latter in shaping codon usage profile in the viral hemagglutinin. The data showed conspicuously that the sequences were A redundant with most codons preferring nucleotide A over others in the third synonymous codon site. The results indicated the pivotal role of compositional pressure affecting codon usage in this virus.